Improved single-site chromium catalysts with electron rich indenyl ligands for the formation of ultrahigh molecular weight polyethylene - Hansen, Helge-Boj; Wadepohl, Hubert; Enders, Markus (European journal of inorganic chemistry, 2021)
Quinolyl functionalized indenyl chromium complexes with different substitution patterns were synthesized and evaluated as single site catalysts in ethylene polymerization. Adding substituents like a fused cyclohexyl ring or a Si(CH3)3 group to the indenyl moiety improve complex stability, solubility and catalytic activity compared to the unsubstituted analogues. Furthermore, the ability to incorporate 1-hexene into the polymer chain increased. Ultrahigh molecular weight polyethylene (UHMW-PE) or linear low density polyethylene (LLD-PE) with very high molecular weight was obtained. Although other catalysts are able to incorporate more 1-hexene only a few systems are known, that combine substantial 1-hexene incorporation with very high activity and such high molecular weights. Consequently, these catalytic systems are attractive candidates in industrial processes for the production of improved polyethylene materials.
First published: 10 February 2021
Gesehen am 24.11.2022